Strategi Komunikasi Pemasaran Pemerintah Daerah Dalam Meningkatkan Kesejahteraan Petani Gambir Pada Program Sentra IKM Kecamatan Sutera - Sarifa Aini; Ria Edlina (CV. ITTC INDONESIA, 2026)
This study aims to analyze the local government’s marketing communication stratergy in the Sentra IKM gambir in Sutera district and examine its effectiveness in improving farmer’s welfare. This research employs a qualitive approach with a descriptive method, utilizing interviews, observation dan documentation as date collection techniques. The findings indicate that the government has designed a marketing communication strategy aimed at increasing product value through downstream processing, quality enhancement and marketing expansion. The implementation involves personal selling, direct marketing, digital marketing and promotional activities through exhibilition. However, audience segmentation and the integration of communication channels have not been fully optimized, resulting in uneven information dissemination. While the strategy has been effective in enhanacing farmer’s capacity and production awareness, it has not fully ensured income stability due to price fluktuations and limited market access. Therefore, the overall marketing communication strategy can be categorized as semi-effective.